Effect of Substrate Feeding Concentration on Initial Biofilm Development in Anaerobic Hybrid Reactor - B. Suraraksa; A. Nopharatana; P. Chaiprasert; S. Bhumiratana; M. Tanticharoen (ASEAN Journal on Science and Technology for Development, 2003)
To elucidate the effect of substrate concentration on biofilm development, glucose concentrations of 500 and 1,000 mg/L were used.  At an early stage, biofilm development at both concentrations was not significantly different (P=0.621).  After removing suspended biomass at 24 operational hours, the biofilm development at high substrate concentration was higher than at lower concentration.  At 72 operational hours, the amounts of attached biomass at low and high glucose feeding were 9.04±1.17 and 28.58±2.72 g VSS/m2, respectively.  The activities of acidogens, acetogens, and methanogens at the low glucose concentration were 0.334, 0.016 and 0.003 g COD/g VSS/h, and those at the high glucose concentration were 0.145, 0.003 and 0.001 g COD/g VSS/h, respectively.  Moreover, the ratio of methanogenic activity at low glucose concentration was higher than at high glucose concentration.  The glucose utilization at low and high feeding concentrations was 33% and 27%, respectively.  These results indicated that rapid biofilm development by using high substrate concentration would be less beneficial if unbalance of methanogenic ratio was found in biofilm.